Przekłady liryki Johna Donne`a na język polski w kontekście biograficznym = Renditions to Polish language of John Donne`s lyrics in biographical context - Banaszak, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author of the article tries to answer the question - to what extent is the knowledge about the biography of the metaphysical poet John Donne useful in the reception of his poety and translations of this poetry into Polish. It can be often seen that some individual components of Donne`s style were shaped under the influence of his personal experience.
Keywords: przekład literacki; poezja; biografia; Donne, John (1572-1631); poetry; biography; literary translations